Socio-political hoaxes in virtual public space: Assertive illocutionary manifestations of dishonesty in a critical pragmatics perspective - Rahardi, R. Kunjana; Firda Utami , Septa (Universitas Ahmad Dahlan, 2024)
Fake news in a socio-political context is a form of language abuse that aims to create chaos and influence public opinion wrongly. The purpose of this study is (1) to describe the purpose of socio-political hoaxes in the public space as a clear manifestation of dishonesty. (2) Describe the purpose of socio-political hoaxes in the public space as a clear manifestation of dishonesty. This study applies a qualitative descriptive approach to explore the complexity of language phenomena in the context of socio-political hoaxes. The research data is a snippet of a speech of socio-political reality on social media. The data collection method is a listening method that involves reading and recording social media content. In the analysis stage, additional language matching methods are applied to connect the language used with the relevant social, cultural, and situational context. The analysis steps carried out include identification, classification, typification, and interpretation. The findings of the embodiment of the form and purpose of this research are presented as follows: (1) Fake content with the aim of provoking and misleading the public; (2) Fake video content with the purpose of misleading and lying; (3) False illustrations with the aim of deceiving the public; (4) False content with the purpose of defaming and deceiving the public; (5) False content with the purpose of inciting and misleading the public; (6) Hoaxes with the purpose of insulting and defaming; (7) False content with the aim of inciting and misleading the public.